Factors Affecting Cheating Behavior at Quetta- Pakistan (Journal of Education and Educational Development, 2023)
Cheating in examinations across the globe is an issue of growing concern. This study argues that the culture of cheating in exams in Balochistan has reduced the efficiency of human resource and has resulted in producing students with high qualifications but less potential in the province. Therefore, it is very importantto explore the factors contributing to cheating in exams and to suggest a course of action to mitigate the menace it poses. A quantitative research method was employed for this study. Similarly, statistical techniques such as correlation and logistic regression were conducted for statistical analysis and explanation of thestudy using SPSS. Theoretically, the study is inspired by rational choice theory. The findings of the study show a significant relationship between personal, institutional, and situational factors. Personal factors that contribute to cheating were found to be students’ desire to excel, low GPA, and slow learning. Institutional factors include the weak administrative role of institutions, poor academic policies, overload on students, and weak performance of the teachers. Situational factors such as the poor management strategy of the examiner, time pressure, and technological tools were found to be instigating students towards cheating. The study suggests that an appropriate exam hall setting, effective monitoring, concept-oriented exams, and a strong honor code can decrease cheating.